Humanization of outgroups promotes justice in carbon allocation. (December 2022) - Huang, Lingling; Liu, Li; Dang, Jianning; Wei, Cong; Liang, Yuan; Gu, Zibei; Li, Jinfeng
Abstract: Understanding the underpinnings of climate justice, especially justice in carbon allocation, is paramount for international cooperation in coping with climate change. Previous work has attempted to promote carbon allocation justice based on a utilitarian theory of justice, but it has backfired. Adopting the per capita approach in defining justice suggested by a Rawlsian theory of justice, the current research addresses the psychosocial processes underlying justice in carbon allocation. Inspired by the social identity approach, we propose that whether people choose to behave justly in carbon allocation originates, in part, from their perceptions about whether an outgroup shares similar humanness with the ingroup. We conducted four studies ( N  = 1326) to test this assumption. The results indicated that humanization increased the allocation of carbon credits to an outgroup (Study 1), increased the amount of carbon credits contributed and decreased free-riding behavior (Studies 2 & 3), and reduced carbon emissions and over-emitting behavior (Study 4) in carbon allocation; the effects were mediated by an expanded scope of justice (Studies 1–4). By identifying the roles of humanization and the scope of justice in carbon allocation justice, this research provides a psychosocial framework for understanding climate justice, which has implications for guiding the priorities of policymakers. Highlights: We explored beneficial effects of humanization of outgroups on justice in carbon allocation. Humanization increased the allocation of carbon credits to an outgroup and the amount of carbon credits contributed. Humanization decreased free-riding behavior and over-emitting behavior. Scope of justice accounted for the effect of humanization on justice in carbon allocation.